Revaluasi Aset Tetap: Accounting Background, Fixed Assets Intensity, Liquidity - Tatik Zulaika; M. Ichsan Diarsyad; Darmae Nasir; Hanna Grahitha Septia (KINDAI, 2023)
The purpose of this paper was to examine the effect of Accounting Background, Fixed Assets Intensity, and Liquidity of Fixed Asset Revaluation. The research method used in this paper is quatitative research. The sampling technique in this study used purposive sampling. The data used in this paper is secondary data in the form of documentation, namely data obtained from company year reports on the Indonesia stock exchange during the 2019-2021 period. The number of samples used in this study were 142 service companies listed on the Indonesian stock exchange in 2019-2021. Then the data that has been obtained was tested by logistic regression analysis using the SPSS version 26 application tool. The results of this study indicate that the Fixed Assets Intensity have a effect on the revaluation of Fixed Assets. Meanwhile, Accounting Background and Liquidity has no effect on the revaluation of Fixed Assets. Keywords: Accounting Background, Fixed Assets Intensity, Liquidity, Fixed Asset Revaluation